THE INFLUENCE OF HUMAN RELATIONS AND PHYSICAL WORK ENVIRONMENT ON THE WORK ETHOS OF WAREHOUSE EMPLOYEES AT PT. TALKINDO SLAKSA ANUGRAH, SOUTH TANGERANG - Endang Susilo Wardani; Eti Ariyanti; Laila Irawati (International Journal Management and Economic, 2025)
This research investigates the impact of human relations and the physical work environment on the work ethic of warehouse employees at PT. Talkindo Selaksa Anugrah, South Tangerang. The study focuses on a population comprising 62 employees in the warehouse department, using a saturated sampling technique where the entire population serves as the sample. This ensures comprehensive representation of the targeted group for reliable results. A quantitative research approach was employed, utilizing an associative method to examine the relationships between variables. Data collection was conducted through structured questionnaires designed with a Likert scale to measure respondents’ agreement levels with various statements related to human relations, physical work environment, and work ethic. The study incorporates both primary data, obtained directly from respondents, and secondary data, sourced from relevant literature. Results indicate that both human relations and the physical work environment significantly and positively affect work ethic, both individually and collectively. This study highlights the critical role of fostering interpersonal relationships and maintaining a supportive physical environment in enhancing employee motivation, satisfaction, and overall productivity.